Potential Feed Additives as Antibiotic Alternatives in Broiler Production - Ayalew, Habtamu; Zhang, Haijun; Wang, Jing; Wu, Shugeng; Qiu, Kai; Qi, Guanghai; Tekeste, Ayalsew; Wassie, Teketay; Chanie, Demissie (Frontiers in Veterinary Science, 2022)
This paper aimed to describe the current use scenario, alternative feed additives, modes of action, and ameliorative effects in broiler production. Alternative feed additives have promising importance in broiler production due to the ban on the use of certain antibiotics. The most used antibiotic alternatives in broiler production are phytogenic, organic acids, prebiotics, probiotics, enzymes, and their derivatives. Antibiotic alternatives have been reported to increase feed intake, stimulate digestion, improve feed efficiency, increase growth performance, and reduce the incidence of disease through modulating the intestinal microbiota, immunity systems, inhibiting pathogens, and improving intestinal integrity. Simply, the gut microbiota is the target to raise health benefits and growth-promoting effects of feed additives in the broiler. Therefore, naturally available feed additives are promising antibiotic alternatives for broilers. Then, summarizing the category, mode of action, and ameliorative effects of potential antibiotic alternatives in broiler production may provide more informed decisions for broiler nutritionists, researchers, feed manufacturers, and producers.